Determination of alcohol chill haze in beer: Submitted on behalf of the Analysis Committee of European Brewery Convention - Batchvarov, V.; Kellner, V. (BrewingScience, 2004)
In order to examine the Chapons alcohol chill haze test in beer (3, 4) by nephelometry, a collaborative trial was carried out using six beer samples with different levels of alcohol chill haze. Fifteen laboratories of the members of the EBC Analysis Committee took part in the collaborative trial. The method for determination of alcohol chill haze in beer yields results with satisfactory repeatability (r95) and reproducibility (R95). The EBC Analysis Committee decided to include the method for determination of alcohol chill haze in beer in Analytica-EBC and recommend it as a guideline method.